2015
DOI: 10.1108/pijpsm-01-2015-0008
|View full text |Cite
|
Sign up to set email alerts
|

Measuring police officer and citizen satisfaction: comparative analysis

Abstract: Purpose – The ability of the police to decrease victimization rates, protect human rights and social capital, to generate feelings of safety and to respond to citizens’ calls helps generate positive citizen feelings about the legitimacy of police as a law enforcement institution. Police approaches to reduce crime and violence are based mainly on objective measures, neglecting to assess its performance based on subjective perceptions. The conception that the citizens’ fear of being victims is no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 46 publications
2
17
1
2
Order By: Relevance
“…Phase 5: nomological validity Structural equation modelling was performed using AMOS to evaluate the nomological validity of the relationship between smart policing service quality and its theoretical constructs (Li and Shang, 2020). Several studies have identified the relationships among police service quality, satisfaction and attitudes (Bouranta et al, 2015;Chen et al, 2014). It was previously suggested that consistent service and qualities of smart policing can lead to a better quality of life, satisfaction, trust and continued intention to use the services (Chatterjee et al, 2018;El-Haddadeh et al, 2019;Kankanhalli et al, 2019;Nowak, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Phase 5: nomological validity Structural equation modelling was performed using AMOS to evaluate the nomological validity of the relationship between smart policing service quality and its theoretical constructs (Li and Shang, 2020). Several studies have identified the relationships among police service quality, satisfaction and attitudes (Bouranta et al, 2015;Chen et al, 2014). It was previously suggested that consistent service and qualities of smart policing can lead to a better quality of life, satisfaction, trust and continued intention to use the services (Chatterjee et al, 2018;El-Haddadeh et al, 2019;Kankanhalli et al, 2019;Nowak, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, customers have access to an educational level that allows them to judge any product or service they pay for, while they demand the best possible products and services at the lowest price. Consequently, a company that meets or even exceeds a customer's expectations has a significant competitive advantage [26][27][28]. Therefore, it is important for every company to know who its customers are, what they expect and how adequately their expectations are met.…”
Section: Industrial Customers' Satisfactionmentioning
confidence: 99%
“…Race and ethnicity were also found to be strong determinants of (or correlates with) officer-involved shootings (McElvain & Kposowa, 2008). The more interesting analyses (Bouranta, Siskos, & Tsotsolas, 2015;Chapman, 2012;Lasley, Larson, Kelso, & Brown, 2011;Stultz, Parker, & Lane, 2010) broadened the simple race-behaviors studies and strived to find and quantify the relationship between an officer's race/ethnicity, the officer's affinity toward his or her beat (or community), and the officer's propensity to use appropriate force and be well-respected and well-accepted in the served community. The next section addresses the confluence of police agency racial composition and the racial compositions of the communities each agency serves.…”
Section: Police Officer Racial and Ethnic Characteristicsmentioning
confidence: 99%
“…Ho and Cho 2016 ). Yet many commentators now consider "confidence" to be the most telling and accurate yardstick to employ (although confidence is closely allied with trust) (Antrobus, et al, 2015;Bouranta, et al, 2015;Cao, 2011Cao, , 2015Garcia & Cao, 2005;Hinds, 2009;Jefferis, et al, 2011;Lai & Zhao, 2010;Tankebe, 2010Tankebe, , 2013Zhao, et al, 2015). As one example, Cambridge scholar Justice Tankebe measured the impact of police corruption in Ghana on the public's confidence in that nation's law enforcement (Tankebe, 2010).…”
Section: Measuring Civilian Confidence In Local Law Enforcementmentioning
confidence: 99%